2019
DOI: 10.1007/s11277-017-5053-y
|View full text |Cite
|
Sign up to set email alerts
|

A QoS-Aware Joint Power and Subchannel Allocation Algorithm for Mobile Network Virtualization

Abstract: Doctor of PhilosophyQoS-aware Joint Power and Subchannel Allocation Algorithms for Wireless Network Virtualization by Junyi WEI Wireless network virtualization (WNV) is a promising technology which aims to overcome the network redundancy problems of the current Internet. WNV involves abstraction and sharing of resources among different parties. It has been considered as a long term solution for the future Internet due to its flexibility and feasibility. WNV separates the traditional Internet service provider's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…Instead, Wei et al in [147] take a centralized approach. Specifically, the work in [147] considers multiple InPs and multiple VNOs (analogous to SPs) in the context of WNV. Here, each InP has a given set of users of its own; resources allocated to its own users are referred to as local slices and the total rate across the local slices should be above a given minimum for each InP.…”
Section: Infrastructure Sharing For Decoupled Infrastructure From Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, Wei et al in [147] take a centralized approach. Specifically, the work in [147] considers multiple InPs and multiple VNOs (analogous to SPs) in the context of WNV. Here, each InP has a given set of users of its own; resources allocated to its own users are referred to as local slices and the total rate across the local slices should be above a given minimum for each InP.…”
Section: Infrastructure Sharing For Decoupled Infrastructure From Servicesmentioning
confidence: 99%
“…Actors Approach [30] many InPs -one SP contract theory [147] many InPs -many SPs IP model [156] many InPs -many SPs auction theory [28] many InPs -many SPs MLFG…”
Section: Articlementioning
confidence: 99%
“…The basic function of the system includes a unified code maintenance mechanism to adapt to the current situation that the relevant standards are incomplete and the application is ahead of the standard. When necessary, a number of professional standards are formed on the basis of project construction [11].…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the current research models, methods and technologies of virtual network embedding into physical networks, and drawing future research trends, it is found that the main difference between VNE and previous Internet models is that it is mainly to simplify the embedding problem on large networks. e infrastructure sharing mechanism must contain a module that maps the virtual nodes and links of the virtual network to the computing modules and transmission paths in the physical network, respectively, which is usually called virtual network embedding, and can also be called mapping [18] or configuration [19].…”
Section: Introductionmentioning
confidence: 99%